An Investigation Into the Relationship Between Long-term Posttraumatic Stress Disorder Symptoms and Coping in Australian Volunteer Firefighters. Issue 7 (July 2016) - Doley, Rebekah M.; Bell, Ryan; Watt, Bruce D.
Abstract : Abstract: This study examined the relationship between coping style and long-term posttraumatic stress symptoms in an Australian sample of volunteer firefighters 84 months following a bushfire disaster. A total of 277 firefighters completed 4 questionnaires to assess patterns of psychiatric morbidity. A 2-way repeated-measures analysis of variance was conducted to investigate the effect of time and disorder on coping. Firefighters evidencing distress were more likely to use both problem- and emotion-focused methods of coping. Based on previous research, it was hypothesized that problem-focused coping strategies would be used after 84 months. The use of both problem- and emotion-focused coping may be due to the length of time following this disaster or unique characteristics of firefighters. These data suggest that present coping theories are not sufficient to account for the onset and pattern of psychiatric morbidity within a firefighter sample. The authors declare no conflicts of interest including financial, consultant, institutional, and other relationships that might lead to bias.